Electrocardiogram R-wave is an Unreliable Indicator of Pulse Wave Initialization. Issue 1 (July 2017) - Balmer, Joel; Pretty, Christopher; Kamoi, Shun; Davidson, Shaun; Pironet, Antoine; Desaive, Thomas; Shaw, Geoffrey M.; Chase, J. Geoffrey
Abstract: Pulse wave velocity (PWV) measurements are commonly used to evaluate a patient's arterial stiffness, an indicator of cardiovascular dysfunction. PWV is usually calculated by measuring the pulse transit time (PTT) over a known distance through the arteries. In an experimental study on animals, it is straight forward to measure the PTT using two pressure catheters a known distance apart in the central arteries. However, in a clinical setting it is uncommon for such a direct invasive method to be used. This study aims to identify whether a surrogate measure of PTT could be found without the need for an external device and without being additionally invasive. The aim is to use the time between the R-wave of an electrocardiogram (ECG), and the pulse wave passing one pressure catheter (rPTT), both of which are common in critical care. The analysis was performed using data from four porcine experiments (Pietrain Pigs, 20-29kg) in which ECG, aortic arch pressure and abdominal aortic pressure were measured simultaneously over a range of induced hemodynamic conditions including recruitment manoeuvres (RM), fluid admission and dobutamine admission. From the measured data, the correlation of rPTT and PTT was calculated for each pig and condition. The overall results showed varied correlations across the pigs (r 2 = 0.07 to 0.75). The variability is suspected to be due to two main causes, the first being pig specific response to the interventions. The second cause leading to poor correlation is suspected to be the pre-ejection period (PEP), the time following the ECG R-wave but before ejection of blood from the ventricle. The analysis showed that rPTT was an unreliable measure of PTT and a poor surrogate.